Efecto del tiempo de nitruración en las propiedades mecánicas y microestructurales del acero 4340 (2023)
The following project proposes an analysis of the effect of nitriding time on the mechanical and microstructural properties of 4340 steel. The nitriding treatment consists of introducing nitrogen on the surface of the steel which allows a surface hardening. This thermal process takes place in a temperature range of 400 to 620º C.